Indoor positioning system based on magnetic fingerprinting-images - Ahmed Gamal Abdellatif Ibrhaim; Mostafa Mohamed Ahmed; Andrea Masiero; Adel Zaghloul Mahmoud; Mohamed E. Nasr; Fathi Elsayed Abdelsamie (Bulletin of Electrical Engineering and Informatics, 2021)
In latest years, indoor positioning techniques have gained much attention, because of the absence GPS signal, so this paper shows a low priced mobile mapping system through using the advantages of integrating inertial navigation with smartphone sensors information concerned to a previous training phase with a magnetic map properly computed to more accurate positioning. Thus, areal online data sets were compiled through the use of ultra wide band to furnish an accurate positioning on the whole area of test and compute a trajectory used as a reference. Then, the use of the pedestrian dead reckoning based approach and IMU help to supply external information from the Wi-Fi signal that is used to exploit the received signal strength path loss, which is possibly used to assess the space between the device and access points. Furthermore, these real online data sets have been processed using Matlab to illustrate the different paths of the area of test. Also, using all RSS for every path line, different images were created. Finally, the positioning efficiency that is possible to be realized using information from IMU and UWB accelerated the fingerprinting training phase. So, the graphical analysis is used to summarize the results that match the closest path to the true path using mutual information.